2019
DOI: 10.3390/v11121095
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Innate Sensing of Prototype Foamy Viruses in Myeloid Cells

Abstract: Foamy viruses (FVs) belong to the Spumaretrovirinae subfamily of retroviruses and are characterized by unique features in their replication strategy. This includes a reverse transcription (RTr) step of the packaged RNA genome late in replication, resulting in the release of particles with a fraction of them already containing an infectious viral DNA (vDNA) genome. Little is known about the immune responses against FVs in their hosts, which control infection and may be responsible for their apparent apathogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…ANKRD17 has been shown to physically interact with viral structural and non-structural proteins, however, the functional importance of these interactions is unknown [50,51]. Innate immunity appears to play an important role in controlling FV infections but its role in BFV is almost not understood [52][53][54][55]. Thus, potential downstream target genes of ANKRD17 were analyzed for their response toward BF2-5p miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…ANKRD17 has been shown to physically interact with viral structural and non-structural proteins, however, the functional importance of these interactions is unknown [50,51]. Innate immunity appears to play an important role in controlling FV infections but its role in BFV is almost not understood [52][53][54][55]. Thus, potential downstream target genes of ANKRD17 were analyzed for their response toward BF2-5p miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…This insensitivity to target intercellular dNTPs is because reverse transcription occurs late in the PFV lifecycle, resulting in a fraction of mature virions harboring nearly complete vDNA [137][138][139][140]. PFV virions with complete vDNA are able establish a productive infection in monocytes; however, incomplete reverse transcriptase products (RTIs) trigger a STING-dependent innate immune response in this cell type [141]. As a result, T and B lymphocytes prominently support viral replication in vivo, a tropism that possibly contributes to the apathogenic phenotype of PFV [142,143].…”
Section: Samhd1 Restriction Of Rna Virusesmentioning
confidence: 99%
“…A few studies supported the existence of an early RT step during foamy virus infection upon entry, which is thought to be relevant at low multiplicities of infection [ 82 , 87 ]. The biological relevance of virions with DNA or RNA genomes is controversially discussed, and the precise proportion of these needs to be determined, especially in vivo [ 14 , 67 , 81 , 82 , 86 , 87 , 88 ].…”
Section: Molecular Biology Of Fvmentioning
confidence: 99%
“…Additionally, a new study suggested that pharmacological inhibitors of the IFN-I response enhance the replication of primary gorilla SFVs [ 125 ]. Very recently, using a myeloid cell model, the innate sensing pathways involved in FV infection were described [ 88 ]. Efficient ISG induction was demonstrated by sensing of full-length PFV genomes but not of minimal vectors in the cytoplasm.…”
Section: Innate Immune Sensing Of Foamy Virusesmentioning
confidence: 99%
See 1 more Smart Citation